2020
DOI: 10.2174/1874331502014010345
|View full text |Cite
|
Sign up to set email alerts
|

Dosed Exposure to Low Temperature as a Breeding Background in The Selection of Gene Pool Breeds of Chickens for Viral Vaccines Production

Abstract: Background: One of the ways to utilize the potential of local breeds is to use them as producers of raw materials for the bio-industry (production of vaccines and diagnostics for animals and humans). Methods: Breeding of Russian White (PRWC) laying hens in 5 generations was carried out with the aim of increasing the output of allantois-amniotic fluid of embryos with a selective background (cooling of hatching eggs dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…Water intake was positively correlated with rectal temperature in birds reared under white polymer, as the values of cloacal temperature and water intake were highest throughout the study. This result correlates with the report presented by Vaneekeren N et al and Stanishevshevskaya OL and Fedorava ES [24,11] who stated that one of the ways broilers exchange heat is by increasing their water intake. These results suggest that, higher luminosity stimulated physical activity, the low body temperature allowed better heat exchange, and therefore, there was less need for birds reared under the back polymer light filter to drink water.…”
Section: Environmental and Cloacal Temperature Parameters On Performa...supporting
confidence: 92%
See 1 more Smart Citation
“…Water intake was positively correlated with rectal temperature in birds reared under white polymer, as the values of cloacal temperature and water intake were highest throughout the study. This result correlates with the report presented by Vaneekeren N et al and Stanishevshevskaya OL and Fedorava ES [24,11] who stated that one of the ways broilers exchange heat is by increasing their water intake. These results suggest that, higher luminosity stimulated physical activity, the low body temperature allowed better heat exchange, and therefore, there was less need for birds reared under the back polymer light filter to drink water.…”
Section: Environmental and Cloacal Temperature Parameters On Performa...supporting
confidence: 92%
“…Broiler starter chicks require environmental temperature of 29 -32°C, while environmental temperature of 23 -28°C is needed at the finished phase of the birds [10]. Stanishevshevskaya OL and Fedorava E.S [11] reported that a day-old chicks have difficulty in maintaining their body heat because their thermoregulatory capacity is not well developed. Heat stress has detrimental impacts on physiological function and growth performance, manifesting as lower feed consumption, reduced body weight gain, and lower feed efficiency [12].…”
Section: Introductionmentioning
confidence: 99%
“…In the time of the Soviet Union, RW was the major layer breed used for egg production [10]. Currently, only a small number of cold-tolerant and disease-resistant RW chickens are kept in the gene pool collection [19,20]. Identifying genomic regions affected by natural and artificial selection in breeds with different genetic backgrounds may give an insight into the history of domestication and selection for economically important traits [76][77][78][79].…”
Section: Genomic Trajectories Of Selectionmentioning
confidence: 99%
“…Presently, the small RG population of cold-tolerant RW chickens (25 males and 234 females) is kept in the Genetic Collection of Rare and Endangered Chicken Breeds of the RRIFAGB. In the last two decades, the RW breeding program has been aimed at improved egg production and egg weight and increased yield of vaccine raw material, i.e., extraembryonic (allanto-amniotic) fluid and titers of vaccine viruses in it while maintaining cold tolerance of neonatal chickens [ 15 , 19 , 20 ]. There is also one more RW population maintained at the All-Russian Poultry Research and Technological Institute (ARPRTI) collection farm, Sergiev Posad.…”
Section: Introductionmentioning
confidence: 99%